Democratic Republic of Congo - The Potential for Growth : An Investment Climate Assessment - World Bank (Washington, DC, 2013)
The Democratic Republic of Congo (DRC) is the third most populous county in Sub Saharan Africa and has many natural advantages that would enable it to experience rapid sustained economic growth and rapid poverty alleviation. These include rich and diverse natural resources, such as mining and hydroelectric potential, abundant fertile land, and a large domestic market. The country is emerging from conflict and democratic election, and benefits from significant external capital inflows from export of commodities with surging prices and donor aid, as well as debt relief. Starting from a low base (with GDP per-capita in 2006 about 1/3 of where it was in 1980) an economic rebound would also be expected, and indeed is happening: current GDP growth is hovering around 6 percent. Nevertheless, this level of performance is insufficient to address poverty, with the Millennium Development Goals being mostly out of reach. Growth needs to be accelerated, shared better and sustained over the years to come. While certain countries have been unable to respond to such challenges, others, including Uganda in the 1990s and Mozambique now, have registered impressive results. DRC can also engage on a similar path. In order for sustained shared growth to be realized and for investments to materialize, Government needs to quickly implement a number of regulatory and policy reforms and to develop a more predictable policy environment. It also needs to make sure that all private sector entrepreneurs, not just those in certain sectors benefit from an enabling environment conducive to their activities.